Tunable-wavelength picosecond vortex generation in fiber and its application in frequency-doubled vortex. (12th December 2017) - Zhang, Wending; Wei, Keyan; Wang, Heng; Mao, Dong; Gao, Feng; Huang, Ligang; Mei, Ting; Zhao, Jianlin
Abstract: We present a method for tunable-wavelength picosecond vortex pulse generation by using an acoustically-induced fiber grating (AIFG). The AIFG-driven mode conversion characteristic was activated via a shear-mode piezoelectric transducer that excels in excitation efficiency of acoustic flexural wave and mechanical stability. The linearly-polarized ±1-order picosecond vortex pulse was experimentally generated via AIFG with a uniform coupling efficiency of ∼98.4% from the fundamental mode to the ±1-order vortex mode within the wavelength range 1540 nm ∼ 1560 nm. The topological charge and the linearly-polarized characteristic of the picosecond vortex pulse were verified by examination of the off-axial interference and the polarization angle-dependent intensity, respectively. Furthermore, the picosecond vortex pulse with wavelength tunability was input to a nonlinear BBO crystal to generate a frequency-doubled ±2-order vortex in the wavelength range 770 nm ∼ 780 nm. This technology provides a convenient apparatus for generating a picosecond vortex pulse and the frequency-doubled vortex with wavelength tunability.